PENGARUH BAGI HASIL, NON PERFORMING FINANCING (NPF) DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PT BANK SYARIAH BUKOPIN - Haris Al Amin; Hilmi Hilmi; Elsa Rozana (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
Abstract: This research aims to understand the influence for the results, non performing financing, financing to deposit ratio against profitability of pt bank bukopin syariah. He data used in this research was data quarter 2009-2016 published by bank bukopin syariah in quarter financial report bank bukopin syariah. The process of analysis undertaken is classic test assumptions and next conducted the testing of hypotheses. Statistical methods used is linear regression worship of idols. Based on the research done or, indicate that all variable influential simultaneously to profitability, While the results of the study in partial showed that only one variable just an influential in partial to profitability namely variable profit sharing, While variable non performing financing and financing to deposit ratio has proven to be not influential in partial to profitability in a bank bukopin syariahkeyword : Profit Sharing , Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) , dan Profitability.